The icebound land - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice ;, 2008)
Will and Evanlyn are kidnapped and sent to Skandia aboard a ship. Halt is determined to rescue them even after being expelled from the Rangers.